Postlaparoscopic GnRHagonist Therapy does not Improve Spontaneous Conception Rates of Women with Endometriosis - Tjandraprawira, Kevin D; Djuwantono, Tono (Indonesian Socety of Obstetrics and Gynecology, 2017)
Objective: To investigate the reproductive benefits of combining laparoscopic surgery with GnRH-agonist hormonal therapy in treating women with endometriosis. Methods: This is a non-randomized prospective analytic study of patients with endometriosis conducted in a private hospital in Bandung during the period of January 2014 to December 2015, whom were later followed up after 12-24 months for assessment of post-surgical reproductive performance. A total of 121 patients were enrolled, 60 of which received post-surgical GnRH-agonist hormonal therapy. Results: We discovered that 56 women (46.3%) eventually achieved spontaneous conception after surgery but upon further analysis, it was discovered that GnRH-agonist played no significantly meaningful role in improving the spontaneous pregnancy rates of these patients (OR 1.539; 95% CI 0.750-3.159; p-value 0.239). Furthermore, even though there was a wide range as to when they achieved conception, those untreated with hormonal therapy tended to conceive far more quickly than those who were (5.91 ± 6.28; 8.56 ± 4.24; p-value: 0.011). Conclusion: Post-laparoscopic GnRH-agonist administration to women with endometriosis does not significantly improve their chances of spontaneous conception. In fact, such administration seems to delay it. [Indones J Obstet Gynecol 2017; 5-2: 87-93] Keywords: endometriosis, GnRH-agonist, laparoscopy